Randomised controlled trial of colloid infusions in hypotensive preterm infants. - Emery, E F (1992)
Colloid infusions are often given to treat hypotension in preterm infants. The aim of this work was to assess whether it was the amount of protein or the volume of the colloid infused which accounted for the observed increase in blood pressure. Sixty preterm infants were randomised (20 in each group) to receive 5 ml/kg 20% albumin, 15 ml/kg fresh frozen plasma, or 15 ml/kg 4.5% albumin. All infusions were given at a rate of 5 ml/kg/hour in addition to maintenance fluids. The infants were randomised when hypotensive (systolic blood pressure less than 40 mm Hg for two hours). There was no significant difference in the blood pressure of the three groups before or one hour after beginning the infusion. The mean increase in blood pressure one hour after completing the infusion, however, was significantly lower in infants receiving 20% albumin: 9% compared with 17% in the group receiving 4.5% albumin, and 19% in the group receiving fresh frozen plasma. It is concluded that the volume infused rather than albumin load is important in producing a sustained increase in blood pressure.